How Hiring Financial Advisors in Cross-Border Acquisitions in The BRICS is Driven by The Target Country Institutional Image and Home-Target Distance - Gouveia, Luciana Orozco de (2020)
We examine how the target country’s institutional image and home-host institutional and geographic distance influence the acquirer firms’ hiring financial advisors in cross-border acquisitions (CBAs) in the BRICS. Specifically, we scrutinize whether the acquirer hires financial advisor in the acquirer firm’s country, the target country or a global advisor. We argue that the acquirer is more likely to hire a financial advisor the poorer the institutional image of the target country and the greater the home-host institutional and geographic distance. Using longitudinal data on 642 cross-border acquisitions during 2013-2017 in the BRICS – Brazil, Russia, China, India and South Africa, we empirically test the hypotheses. The findings have important implications for scholars, policymakers and managers. Our results confirm that: acquirer firms are more likely to hire a financial advisor in the acquirer’s country to advise a cross-border acquisition the greater the institutional distance between the countries. And, that acquirer firms are more likely to hire a global financial advisor to advise a cross-border acquisition the greater the geographic distance between the countries.